Effect of pollen source on germination of Vanilla planifolia, V. pompona (Orchidaceae), and their interspecific hybrids - José Martín Barreda-Castillo; Emerson Ricardo Pansarin; Juan L. Monribot-Villanueva; Miguel Ángel Lozano-Rodríguez; José A. Guerrero-Analco; Rebeca Alicia Menchaca-García (Botan‪ical Sciences)
Background: Vanilla planifolia and V. pompona exhibit low seed germination rates. Although their fruits are obtained through manual self-pollination, the effect of intra- and interspecific cross-pollination on their fruits and seeds remains unknown. Hybrids organisms are considered potential alternatives to traditional cultivation.